2011
DOI: 10.1002/cncy.20139
|View full text |Cite
|
Sign up to set email alerts
|

p16/Ki‐67 dual‐stain cytology in the triage of ASCUS and LSIL Papanicolaou cytology

Abstract: Most human papillomavirus (HPV) infections are transient. 1 Among other things, unnecessary overtreatment can cause unnecessary future pregnancy complications, but an approach to persistent HPV infection that is too cavalier may result in unacceptably high rates of cervical carcinoma. 2 Cytologists recognize some of the morphologic changes in Papanicolaou (Pap) tests with an excellent specificity, but a single test is associated with a low sensitivity (70%). Screening specificity is greatly improved by the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…It was interesting to note that the combination of all 13 HPV loads showed no improvement in either the sensitivity or specificity of the p16/Ki-67 test for the prediction of CIN or more severe lesions. However, amongst those patients with HPV-16 and/or 58 infection, a combination of the HPV-16 and/or 58 DNA load with p16/Ki-67 staining increased the sensitivity of the detection of CIN1+ and CIN2+ lesions, though p16 and Ki-67 tests were proven to be a highly sensitive method to estimate CIN2+ cytological cases [9, 22, 23]. Whilst the combination of HPV-16 and/or 58 DNA loads achieved only a modest improvement in the detection of CIN3+, the elevated expression of p16/Ki-67 closely correlated with severe neoplastic lesions or more severe HPV positive cases [9, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…It was interesting to note that the combination of all 13 HPV loads showed no improvement in either the sensitivity or specificity of the p16/Ki-67 test for the prediction of CIN or more severe lesions. However, amongst those patients with HPV-16 and/or 58 infection, a combination of the HPV-16 and/or 58 DNA load with p16/Ki-67 staining increased the sensitivity of the detection of CIN1+ and CIN2+ lesions, though p16 and Ki-67 tests were proven to be a highly sensitive method to estimate CIN2+ cytological cases [9, 22, 23]. Whilst the combination of HPV-16 and/or 58 DNA loads achieved only a modest improvement in the detection of CIN3+, the elevated expression of p16/Ki-67 closely correlated with severe neoplastic lesions or more severe HPV positive cases [9, 23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Use of these potential predictors should be seriously considered in the management of patients with equivocal cytology. Schmidt et al [49,50] reported that p16/Ki-67 dual-stain cytology showed high sensitivity and specificity for the detection of underlying CIN2+ in women with ASCUS and LSIL in Pap cytology. Furthermore, Petry et al [51] reported that p16/Ki-67 dual-stained cytology may help identify underlying high-grade disease in Pap-negative HPV-positive women.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining of p16 has proved to be especially useful for distinguishing CIN from regenerative atypias, immature metaplasia, and atrophic epithelium (43,44), contributing to a significant increase in the accuracy and reproducibility of the diagnosis (16)(17)(18)20,37,40). Some studies have showed that p16-positive expression is a potential predictor of both progression of the low-grade lesions (19,37) and survival outcome after chemoradiation therapy for advanced-stage invasive cervical carcinoma (45).…”
mentioning
confidence: 99%